The Philosophical Foundation of Rahn Financing in Advancing Agricultural Capital - Khasbiyulloh Rifqi Zidane; Ismatul Khayati (TATHO: International Journal of Islamic Thought and Sciences, 2026)
Access to capital is not only an economic necessity but also a matter of distributive justice and social inclusion for smallholder farmers, who remain underserved by conventional financial institutions. Collateral-oriented banking systems and dependence on informal usurious lending continue to create structural barriers that hinder sustainable agricultural development and conflict with the ethical values of Islamic finance. This study investigates Rahn financing implemented by KSPPS BMT Mandiri Sejahtera Dukun Branch as a sharia-compliant and ethical model for agricultural capital provision. Using a qualitative approach based on literature review, document analysis, and descriptive–analytical methods, the research examines the financing mechanism, contractual integration, and development of the Pertanian Barokah (TABUR) product. The findings show that the integration of Qard, Rahn, and Ijarah enhances accessibility, strengthens trust, and promotes shared responsibility between the institution and farmers. Membership growth during 2020–2024 demonstrates the model's social acceptance and practical relevance. The study concludes that Rahn financing represents a value-based paradigm that advances financial inclusion, community empowerment, and equitable agricultural development while providing practical insights for farmer-oriented Islamic microfinance